Mahr and Walimah in Contemporary Islamic Law: Bridging Normative Principles and Social Practice - Aya Ragab; Aya Said (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study examines the practical interpretation of mahr and walimah within the perspective of Islamic law as essential components of marriage values in Muslim societies. The purpose of this research is to analyze how mahr and walimah function not only as ceremonial traditions but also as legal, ethical, and social instruments that strengthen marital relationships and communal harmony. Theoretical framework: The theoretical framework of this study is based on Islamic family law and the concept of maqasid al-shariah, particularly the principles of justice, responsibility, moderation, dignity, and social welfare in marriage practices. Literature review: The literature review demonstrates that previous studies mostly discuss mahr and walimah separately, focusing either on jurisprudential regulations or socio-cultural dimensions. However, limited research examines both practices simultaneously as practical manifestations of Islamic marriage values in contemporary Muslim life. This study therefore fills the gap by integrating normative Islamic legal analysis with socio-religious interpretations of marriage practices in Muslim-majority societies. Methods: This research employs a qualitative methodology using normative and socio-religious approaches. The normative approach analyzes Islamic legal sources, including the Qur’an, Hadith, and classical jurisprudence related to marriage obligations and ethics. Meanwhile, the socio-religious approach examines how Muslim communities implement and interpret mahr and walimah within changing social and cultural contexts. Data were collected through literature study from books, journal articles, and previous scholarly works concerning Islamic family law and marriage traditions. Results: The findings reveal that mahr symbolizes commitment, protection, and financial responsibility, while walimah represents gratitude, social legitimacy, and communal solidarity. Nevertheless, modernization and consumer culture have transformed these practices into symbols of prestige and economic competition in some Muslim societies. Implications: The study implies that Islamic law should be understood as a dynamic moral framework capable of guiding contemporary marriage practices toward simplicity, justice, and social balance. Novelty: The novelty of this research lies in its integrative analysis of mahr and walimah as interconnected practical interpretations of marriage values within the framework of Islamic law and contemporary Muslim social realities.